Canada : Financial Sector Assessment Program-Basel Core Principles for Effective Banking Supervision-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report, 2014)
This paper focuses on the IMF report on detailed assessment of observance of Basel Core Principles (BCP) for effective banking supervision in Canada. The Canadian banking supervisor (OSFI) adopts a close and cooperative approach that supports the close network of federal authorities in identifying and seeking to mitigate prudential risks to the federal system. As a world-leading regulator, OSFI could be expected to issue a comprehensive suite of risk management standards to be available to all banks, even if at a relatively high level or based largely on Basel Committee for Banking Supervision guidance.